Adoption rationales and effects of off-grid renewable energy access for African youth: A case study from Tanzania. (May 2021) - Simpson, Nicholas Philip; Rabenold, Colton James; Sowman, Merle; Shearing, Clifford D.
Abstract: Inclusive energy access remains elusive globally. Centrally planned energy infrastructures tend to neglect marginalised and disparate populations while upfront costs make it rare for lower-income actors to adopt off-grid renewable energy. This article identifies one emerging response by low-income actors to secure access to through solar photovoltaic energy and an innovative micro-finance enterprise. The AMP framework (awareness, motivation and pathways) is used to explore how and why Tanzanian youths are adopting solar photovoltaic energy and with what effects. Qualitative interviews and field observations indicate awareness and motivational factors of technology, cost, warranty and service influence initial adoption decisions. Nodes of off-grid renewable energy associate with co-benefits of poverty reduction, low-carbon energy access and diversification away from livelihoods that are highly vulnerable to climate change. Framed as a 'pathway', the innovative financing mechanism in this case presents an inclusive model of energy access. These findings extend the AMP framework to include consideration of obstacles within the notion of pathways. The case highlights a potential model for energy access and emerging nodes of decentralised and distributed energy modalities, that are potentially more climate resilient, as low-income actors seek to secure access. Highlights: Adoption rationales play a key role in cascading uptake of renewable energy. Innovative finance overcomes prohibitive start-up costs for Solar PV. Low-income entrepreneurs improve their lives with energy access. Private nodes of energy security overcome systemic geographies of energy poverty. Overcoming identifiable obstacles enables new capabilities to be realised. Graphical abstract: Image 1